French Islamophobia: The Impact of Islamophobia on The Lives of Muslim Women in France - Agus Nilmada Azmi; Aufa Rahadatul Aisy (UIN Syarif Hidayatullah Jakarta, 2023)
Islamophobia is not a new phenomenon. Scholars and authors have been portraying Islam negatively for a long time. Islamophobia was prevalent during the European colonial era and reappeared with a vengeance following the 9/11 attacks, which gave rise to the